The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fgene.2023.1099541
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics and health disparities, are we helping?

Abstract: Pharmacogenomics has been at the forefront of precision medicine during the last few decades. Precision medicine carries the potential of improving health outcomes at both the individual as well as population levels. To harness the benefits of its initiatives, careful dissection of existing health disparities as they relate to precision medicine is of paramount importance. Attempting to address the existing disparities at the early stages of design and implementation of these efforts is the only guarantee of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…SNP analysis and pharmacogenetic‐based opiate prescribing offers a much more precise and biologically driven approach which could reduce the racial and ethnic bias in opiate prescribing practices 12‐16 . Evidence of the impact of different SNP's in opiate drug response is growing.…”
Section: Figurementioning
confidence: 99%
“…SNP analysis and pharmacogenetic‐based opiate prescribing offers a much more precise and biologically driven approach which could reduce the racial and ethnic bias in opiate prescribing practices 12‐16 . Evidence of the impact of different SNP's in opiate drug response is growing.…”
Section: Figurementioning
confidence: 99%
“…In pharmacogenomics, the study of how individual genetic variations influence drug responses has led to personalized drug prescriptions, minimizing adverse drug reactions, and improving treatment efficacy. Existing health disparities, as they intersect pharmacogenomic research and implementation, are being identified [ 21 ].…”
Section: Precision Medicine and Public Healthmentioning
confidence: 99%